2008
DOI: 10.1002/anie.200801260
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Primer Extension in Seconds

Abstract: Rapid extention: Catalysis by pyridine accelerates template‐directed chemical primer extension to t1/2<1 min for all four nucleotides (A/C/G/T). For C and G, greater than 99 % conversion is observed after 30 s (see picture). These sequence‐selective reactions open up new avenues for the interrogation of DNA sequences and chemical replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Many of the thermodynamic and kinetic parameters associated with nonenzymatic RNA replication have been quantitatively determined (10)(11)(12)(13)(14). Until recently, the general assumption has been that nonenzymatic primer extension with activated mononucleotides involves classical S N 2 nucleophilic substitution, in which the nucleophilic 3ʹ-hydroxyl group of the primer attacks the activated phosphorus center of the adjacent template-bound monomer via an in-line mechanism (15).…”
mentioning
confidence: 99%
“…Many of the thermodynamic and kinetic parameters associated with nonenzymatic RNA replication have been quantitatively determined (10)(11)(12)(13)(14). Until recently, the general assumption has been that nonenzymatic primer extension with activated mononucleotides involves classical S N 2 nucleophilic substitution, in which the nucleophilic 3ʹ-hydroxyl group of the primer attacks the activated phosphorus center of the adjacent template-bound monomer via an in-line mechanism (15).…”
mentioning
confidence: 99%
“…Work from our laboratory has extended this concept to the transcription of DNA into a complementary threose nucleic acid (TNA) polymer (10)(11)(12). More generally, the formation of Watson-Crick basepaired duplexes between different nucleic acids suggests that information transfer should be possible between many different nucleic acids, including variants such as 3′-amino RNA and DNA (13)(14)(15), 2′-amino RNA and DNA (16,17), 4′-3′ lyxopyranosyl-NA (18), glycerol nucleic acid (GNA) (19), TNA (20), and others. As long as two polymers can base-pair with each other, it seems reasonable that a mixed polymer containing monomers of each type could still engage in base-pair mediated replication.…”
mentioning
confidence: 99%
“…and coworkers of the extension of primers ending in a 3′-amino nucleotide show that the template-directed primer extension reaction can be very fast, and can occur with relatively high fidelity on both RNA and DNA templates (8,10). We have recently shown that short homopolymeric RNA and DNA templates can be very rapidly copied by nonenzymatic primer extension in the presence of 2-methylimidazole-activated 3′-amino nucleotides (7).…”
Section: Significancementioning
confidence: 99%
“…Obviating the requirement for a polymerase greatly simplifies the task of creating and assembling the components of an artificial cell, and thus of constructing simple living systems from inanimate materials. We and others have therefore explored the synthesis of a variety of phosphoramidatelinked nucleic acids, their corresponding amino-sugar monomers, and the characterization of nonenzymatic template-directed primer extension reactions in these systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Among these systems, we have examined 2′-amino versions of the acyclic glycerol nucleic acid (5), 2′-amino-2′,3′-dideoxyribonucleic acid (4,6), and 3′-amino-2′,3′-dideoxyribonucleic acid (7).…”
mentioning
confidence: 99%